Prediction of intermediate band in Ti/V doped γ-In2S3. Issue 3 (6th January 2022) - Jebasty, R. Mariyal; Sjåstad, Anja Olafsen; Vidya, R.
Abstract : We find the band structure of In1.5 V0.5 S3 with HSE functional, where the vanadium atom introduces an intermediate band inside the forbidden gap in the γ-phase of In2 S3 . Abstract : Materials with an intermediate energy band (IB) introduced in the forbidden gap are viable alternatives to tandem configurations of solar cells for increasing the photon-conversion efficiency. One of the aspiring designs proposed for the intermediate band concept is hyperdoped (Ti, V):In2 S3 . Being very important in copper indium gallium sulfide (CIGS) solar cells, indium thiospinel (In2 S3 ) is known for its three different temperature as well as pressure, polymorphs. The most stable β-In2 S3 was experimentally shown to have an isolated intermediate band (IB) and exhibits sub-band gap absorption due to the completely filled IB after V-doping. Though experimental observation holds a positive signature, recent DFT studies did not show a metallic intermediate band for the V dopant in the 3+ charge state. In order to clarify this, we have taken incentive from experimental XRD analysis that V-doped β-In2 S3 shows peaks from disordered In vacancies (either α or γ), in addition to the ordered In vacancies expected. Hence, we have carried out state-of-the-art DFT based computations on pure and Ti, V-doped In2 S3 in the γ-phase which has not been studied yet. We considered the Ti and V dopants in various charge states. Our theoretical study including hybrid functional, does in fact find the IB in V-doped γ-In2 S3 . However, at equilibrium the IB lies in between the Fermi level ( E F ) and conduction band minimum (CBM).